2002
DOI: 10.1046/j.0014-2956.2001.02695.x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate recognition and fidelity of strand joining by an archaeal DNA ligase

Abstract: We have previously identi®ed a DNA ligase (Lig Tk ) from a hyperthermophilic archaeon, Thermococcus kodakaraensis KOD1. The enzyme is the only characterized ATP-dependent DNA ligase from a hyperthermophile, and allows the analysis of enzymatic DNA ligation reactions at temperatures above the melting point of the substrates. Here . Using various 3¢ hydroxyl group donors (L-DNA) and 5¢ phosphate group donors (R-DNA), we could detect ligation products as short as 16 nucleotides, the products of 7 + 9 nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Different DNA ligases display distinct patterns of fidelity, with respect to how well the ligase discriminates and the hierarchy of which mispairs are or are not accepted by the ligase (Tomkinson et al 1992;Husain et al 1995;Shuman 1995;Luo et al 1996;Sriskanda and Shuman 1998;Bhagwat et al 1999;Tong et al 2000;Nakatani et al 2002;Lamarche et al 2005;Wang et al 2007a). The consistent theme is that DNA ligase fidelity is greatest on the 3 ′ -OH side of the nick.…”
Section: Resultsmentioning
confidence: 65%
“…Different DNA ligases display distinct patterns of fidelity, with respect to how well the ligase discriminates and the hierarchy of which mispairs are or are not accepted by the ligase (Tomkinson et al 1992;Husain et al 1995;Shuman 1995;Luo et al 1996;Sriskanda and Shuman 1998;Bhagwat et al 1999;Tong et al 2000;Nakatani et al 2002;Lamarche et al 2005;Wang et al 2007a). The consistent theme is that DNA ligase fidelity is greatest on the 3 ′ -OH side of the nick.…”
Section: Resultsmentioning
confidence: 65%
“…We assayed each of the four substrates having an insertion of the four nucleotides at the nick site and found that none of these were adenylated by the ligase enzyme. Ligation of substrates with nucleotide insertions on 3′-side of the nick has been investigated for T. kodakaraensis, A. archaeal and T. thermophilus DNA ligases, and also showed negligible ligation activities (4,43,44). It has been also reported that DNA ends with nucleotide protrusion can be ligated to blunt ends by T4 DNA ligase under certain conditions, but as expected with low efficiency (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…1B and 2B). In contrast, DNA ligases are generally biased in their fidelity of mispair sealing, being highly sensitive to 3=-OH mispairs and comparatively tolerant of 5=-PO 4 mispairs (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54).…”
Section: Resultsmentioning
confidence: 99%